Analisis Pola Nilai Akademik Siswa MA Dengan Boarding Di Pondok Pesantren Tradisional Dengan Menggunakan Formal concept analysis - Azizah, Nur; Hidayat, Taufiq; Rahmadi, Ridho (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2020)
Traditional boarding schools still look very minimal in general (non-religious) learning. This can be caused by the absence of learning that focuses on these general lessons in the pesantren, there is not enough learning for general lessons to implement them. With the aforementioned causes, it will be carried out collecting and analyzing the academic value patterns of MA students with boarding conducted using the formal concept analysis method. The purpose of this study was to get an overview of the academic abilities of MA students in traditional huts, especially for general (non-religious) subjects. The results of the analysis can be used for policy improvement recommendations for boarding schools by increasing the ability of students in general subjects.